ECOLOGY AND ECONOMICS OF THE PROCESSES OF END GASES CLEANING AFTER ARC STEEL-MAKING FURNACES - E. A. Bajdalov (Литьë и металлургия, 2009)
The matters of ecology and economics of the processes of end gases cleaning after arc steel-making furnaces are touched upon.